If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 13 = 0 Reorder the terms: 13 + -5x = 0 Solving 13 + -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -5x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -5x = 0 + -13 -5x = 0 + -13 Combine like terms: 0 + -13 = -13 -5x = -13 Divide each side by '-5'. x = 2.6 Simplifying x = 2.6
| 9t^2+18t-72=0 | | 2x+13=-4-17 | | 6x^2+5x=8 | | 20+2y-5=12y-10-5y | | y-9=3(x-4) | | y-9=#9x-4) | | -11y+1=-109 | | x^2+y^2+14x-16y+48=0 | | 4a^2+8a=24 | | 0.08(y-9)+0.06y=0.02y-0.09(20) | | 2n+19= | | 3x-5+x=27 | | 20=a(2b+c) | | 2x+1=8(x-3)+6x | | 0.02(7t+6)=0.14(t+3)-0.30 | | -11y+1=109 | | (2x-6)(2x-5)=(4x+1)(x-4) | | 18=-66 | | 18=-66 | | 0.06(y-7)+0.16y=0.04y-0.003(50) | | -20x+100+x^2=0 | | 3(4x-2)-10=5x-2 | | -4x+6=4x+2 | | 3x+6=9X+10 | | 8x-(4x+20)=8 | | 2(h+5)-3(h-2)=5(2h+1) | | 3(x-6)=x-22 | | (25+3x)=(2x+30) | | 17x-114=13x+62 | | 2x-8+9x=8x+6-4x | | 5x+x=24000000 | | 3(3y+3)=7+3y |